2007
DOI: 10.1677/joe-07-0172
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of Per1 expression by estradiol and progesterone in the rat uterus

Abstract: It has been established that estrogen can alter circadian rhythms in behavior and endocrine physiology in rodents. The uterus is a reproductive organ that is critically dependent on regulation by ovarian steroids. Here, we examined the expression of Per1 in different compartments of the uterus, and explored whether the ovarian steroids could regulate Per1 expression employing ovariectomized rat uterus. RT-PCR analysis showed that Per1 was cyclically expressed in the uterus. As revealed by in situ hybridization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 42 publications
1
47
0
1
Order By: Relevance
“…Further studies are required to determine the mechanisms by which pregnancy-induced changes in central and peripheral clocks occur, but a role for the highly dynamic hormonal milieu of pregnancy seems likely. Indeed, a number of clock genes contain estrogen and progesterone response elements within their promoter regions (Nakamura et al 2005, He et al 2007, Nakamura et al 2010, and ERa, ERb and PR are expressed within the SCN (Blaustein & Wade 1978, Blaustein et al 1988, Vida et al 2008. Previous studies have also shown that clock gene expression is influenced by estradiol in the SCN (Nakamura et al 2001, Nakamura et al 2005 and by progesterone in the uterus (He et al 2007, Nakamura et al 2010, Rubel et al 2012.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies are required to determine the mechanisms by which pregnancy-induced changes in central and peripheral clocks occur, but a role for the highly dynamic hormonal milieu of pregnancy seems likely. Indeed, a number of clock genes contain estrogen and progesterone response elements within their promoter regions (Nakamura et al 2005, He et al 2007, Nakamura et al 2010, and ERa, ERb and PR are expressed within the SCN (Blaustein & Wade 1978, Blaustein et al 1988, Vida et al 2008. Previous studies have also shown that clock gene expression is influenced by estradiol in the SCN (Nakamura et al 2001, Nakamura et al 2005 and by progesterone in the uterus (He et al 2007, Nakamura et al 2010, Rubel et al 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a number of clock genes contain estrogen and progesterone response elements within their promoter regions (Nakamura et al 2005, He et al 2007, Nakamura et al 2010, and ERa, ERb and PR are expressed within the SCN (Blaustein & Wade 1978, Blaustein et al 1988, Vida et al 2008. Previous studies have also shown that clock gene expression is influenced by estradiol in the SCN (Nakamura et al 2001, Nakamura et al 2005 and by progesterone in the uterus (He et al 2007, Nakamura et al 2010, Rubel et al 2012. Moreover, the clock gene expression can be regulated by corticosterone, as glucocorticoid response elements are present within the promoter regions of Per1, Per2 and Rev-erba (Balsalobre et al 2000, Yamamoto et al 2005, So et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…These molecular rhythms have also been found in peripheral organs including female reproductive tissues such as the ovary [64,65], uterus [66][67][68], and oviducts [69] (Figure 1).…”
Section: Clock Genes and Reproductionmentioning
confidence: 78%
“…This suggests that the glucocorticoid response element (GRE) and cAMP response element (CRE) sites in the rat Per2 promoter are operative and transactivate the transcription of the Per2 gene (Travnickova-Bendova et al, 2002;Yamamoto et al, 2004). Although the second oscillation in the stroma cells was delayed compared to that in the ovarian cells (He et al, 2007c), the circadian oscillator was operative with approximately 24 h per cycle. In contrast, the stroma cells from eCG-primed rats exhibited an irregular rhythm of Per2 oscillation with a smaller trough (Fig.…”
Section: Circadian Rhythm In Uterine Cells Under Hormonal Stimulationmentioning
confidence: 93%
“…The circadian clock system may contribute to the progress of follicular development, luteinization and luteolysis, and steroid hormone-induced proliferation and differentiation of uterine cells through fluctuating hormones. Recently, there is a growing body of evidence that circadian clock genes are expressed in reproductive tissues including the ovary and uterus (Johnson et al, 2005;Nakamura et al, 2005;Fahrenkrug et al, 2006;Dolatshad et al, 2006;Karman & Tischkau, 2006;He et al, 2007aHe et al, , 2007bHe et al, , 2007cNakao et al, 2007;Hirata et al, 2009;Sellix & Menaker, 2010;Uchikawa et al, 2011). Many regulatory elements are located at the upstream of clock genes, such as steroid hormone response element half-sites and the adenosine 3',5'-cyclic monophosphate (cAMP) response element site as well as E-box and D-box elements.…”
Section: Introductionmentioning
confidence: 99%